407 Incidental Focal Intrahepatic Duct Dilatation (FIDD) – A Finding That Mandates Further Investigation That May Include Liver Resection. (4th May 2021) - Kumar, N; Kumar, A; Mondal, D
Abstract: Background: The increasing use of imaging has led to incidental findings in the liver. The Western experience of managing focal intrahepatic duct dilatation (FIDD) is not well recorded. We present our experience based on a large prospectively maintained database at a tertiary hepatobiliary surgical unit. Method: Patients with liver resection for FIDD between January 2003-December 2019 were retrospectively identified from the liver unit database. The demographics, symptomatology, blood test results, imaging, type of liver resection, morbidity, mortality, and histology of resected specimens were recorded. Results: 9 patients had FIDD among 994 liver resections performed (0.9%). 6 patients were asymptomatic, 2 upper abdominal pain and 1 recurrent gram-negative sepsis. Liver function tests were normal in all patients. Two patients had cholangiocarcinoma (CCA), 4 intrahepatic stones, 1 intraductal papillary neoplasm of bile duct (IPN –B) and 2 benign strictures. Conclusions: FIDD is rare in the Western population. Most patients are asymptomatic with an incidental finding of FIDD on cross-sectional imaging. Differentiating benign and malignant pathology is difficult warranting liver resection in fit patients to resolve the diagnosis. Liver resection is safe and can be potentially curative in patients with a neoplasm, which can occur in 30% of patients with FIDD.